Five cases of alpha chain disease. Issue 12 (December 1972) - Doe, William F.; Henry, K.; Hobbs, J. R.; Jones, F. Avery; Dent, C. E.; Booth, C. C.
Abstract : Five patients suffering from alpha chain disease are described. Clinically the patients presented with clubbing and the symptoms of malabsorption. There was a characteristic, predominantly plasma cell infiltrate of the wall of the small intestine. Spread of the plasmacytosis beyond the small intestine to bone marrow (1), peripheral blood (1), and probably the nasopharyngeal lymphoid tissue (1) is described. Fragments of the heavy chain of IgA (alpha chain) were found in serum (5), urine (3), jejunal fluid (2), and saliva (1). The jejunal biopsy of one patient was shown to synthesize free alpha chain in tissue culture. A new and simple immunoselection technique for the identification of free alpha chain is described. Marked clinical remissions were achieved in two patients treated with intermittent cytotoxic and steroid therapy, and in a third patient who received intermittent cytotoxic therapy and tetracycline.